2005
DOI: 10.1017/s003329170500499x
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning in adult ADHD: a meta-analytic review

Abstract: Background. Several theoretical explanations of ADHD in children have focused on executive functioning as the main explanatory neuropsychological domain for the disorder. In order to establish if these theoretical accounts are supported by research data for adults with ADHD, we compared neuropsychological executive functioning and non-executive functioning between adults with ADHD and normal controls in a meta-analytic design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
148
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(184 citation statements)
references
References 59 publications
14
148
1
2
Order By: Relevance
“…Similarly, the excessive inhibition failures and normal RTs in the ADHD/combined sample resemble past findings (Boonstra et al, 2005;Lijffijt, Kenemans, Verbaten, & van Engeland, 2005) for samples composed entirely or partly of adults with the ADHD/combined subtype.…”
Section: Performancesupporting
confidence: 76%
“…Similarly, the excessive inhibition failures and normal RTs in the ADHD/combined sample resemble past findings (Boonstra et al, 2005;Lijffijt, Kenemans, Verbaten, & van Engeland, 2005) for samples composed entirely or partly of adults with the ADHD/combined subtype.…”
Section: Performancesupporting
confidence: 76%
“…The time in seconds to complete each trial was registered. As dependent variable, a difference score was calculated by subtracting the time needed for completion of the Color Block condition from the Color-Word Interference condition (Boonstra et al, 2005).…”
Section: Inhibition Was Measured With the Stroop Color-wordmentioning
confidence: 99%
“…A clinical evaluation of symptoms and impairments of patients with ADHD benefits from an objective assessment of neuropsychological functions using standardized psychometric tests. Most theories on neuropsychological functions of adults with ADHD proposed a primary deficit of inhibitory executive functions (Barkley, 1997;Castellanos, Sonuga-Barke, Milham, & Tannock, 2006;Tannock, 1998) which resulted in a large body of research examining various functions associated with executive control, including focused attention, divided attention, vigilance, working memory, inhibition, set-shifting, verbal fluency, and problem solving (Boonstra, Kooij, Oosterlaan, Sergeant, & Buitelaar, 2010;Boonstra, Oosterlaan, Sergeant, & Buitelaar, 2005;Dinn, Robbins, & Harris, 2011;Fuermaier et al, 2015;Hervey, Epstein, & Curry, 2004;Lange et al, 2014;Schoechlin & Engel, 2005;O. Tucha et al, 2005, L. Tucha et al, 2008, 2009.…”
mentioning
confidence: 99%
“…First, the predictive validity of individual-level impairments on any one task for determining diagnosis has been poor (Barkley & Fischer, 2011;Boonstra et al, 2005;Schoechlin & Engel, 2005). For example, Barkley and Fischer (2011) found that EF tasks shared less than 4% of the variance with ADHD symptom severity, indicating that performance on EF tasks did not significantly predict the severity of ADHD symptoms and therefore might not be a valid indicator for identifying ADHD.…”
Section: Measuring Ef Impairments In Adulthoodmentioning
confidence: 99%
“…However, results have been inconsistent, as other work has failed to find any EF deficits among adults with ADHD (Johnson et al, 2001;Weyandt, Linterman, & Rice, 1995). In fact, one study estimated that only about 30% of adults diagnosed with ADHD appear to have EF deficits when measured by performance-based tasks (Brown, 2006), and the predictive validity of EF performance on any one task appears to be poor (Boonstra, Oosterlaan, Sergeant, & Buitelaar, 2005). Several factors may account for these disparate results regarding the role of EF deficits in adult ADHD, including IQ (Antshel et al, 2010;Jung, Yeo, Chiulli, Sibbitt, & Brooks, 2000;Mahone et al, 2002) and methodological inconsistencies across studies (e.g., size of battery and domains assessed; see Woods, Lovejoy, & Ball, 2002).…”
mentioning
confidence: 97%